Aaron's Rod. - Lawrence, D. H. (Floating Press, 1922)
In Aaron's Rod, literary master D.H. Lawrence spins an engaging picaresque tale of the talented English amateur flutist Aaron Sisson and his travels. Aaron escapes a life of drudgery and a loveless marriage and journeys to Italy, crossing paths with a writer who many critics regard as an autobiographical stand-in for Lawrence himself along the way.